An α-helical peptidomimetic scaffold for dynamic combinatorial library formation. Issue 2 (28th November 2016) - Busschaert, Nathalie; Thompson, Sam; Hamilton, Andrew D.
Abstract : A novel oligobenzamide-based α-helix mimetic was designed and synthesised with either imine or hydrazone functionalities that serve both to pre-organise the side-chain vectors to mimic the i, i + 4 and i + 7 residues of an α-helix, and to allow for the facile creation of dynamic libraries. Abstract : A novel oligobenzamide-based α-helix mimetic was designed and synthesised with either imine or hydrazone functionalities that serve both to pre-organise the side-chain vectors to mimic the i, i + 4 and i + 7 residues of an α-helix, and to allow for the facile creation of dynamic libraries.